2018
DOI: 10.21475/ajcs.18.12.07.pne780
|View full text |Cite
|
Sign up to set email alerts
|

Morphological changes recorded in different phenophases of sugarcane plants subjected to water stress in tropical field conditions

Abstract: Nowadays, water deficit is one of the major environmental stress issues affecting sugarcane crops around the world. It has been causing significant production decrease due to the increased mortality rates generated by water stress in sugarcane plantations. The aim of the current study is to assess sugarcane morphological and yield responses during different phenophases of sugarcane varieties when plants are subjected to drought stress in the fields of a tropical region. Six sugarcane varieties, namely: SP79-10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Drought is one of the main climatic factors that currently affects the world's cultivated areas and reduces the crop yielding, including sugarcane (Endres et al, ; Jangpromma et al, ; Silva et al, ; Zhao & Li, ). Moreover, current climate change may increase the effects of drought and hence reduce the availability of water for agriculture (Abdallah, Moses, & Prakash, ).…”
Section: Introductionmentioning
confidence: 99%
“…Drought is one of the main climatic factors that currently affects the world's cultivated areas and reduces the crop yielding, including sugarcane (Endres et al, ; Jangpromma et al, ; Silva et al, ; Zhao & Li, ). Moreover, current climate change may increase the effects of drought and hence reduce the availability of water for agriculture (Abdallah, Moses, & Prakash, ).…”
Section: Introductionmentioning
confidence: 99%
“…In sugarcane, there has been a lack of research under hydroponics, even though drought is identified as a main factor to reduce leaf area under field (Begum et al, 2012;Zhao et al, 2012) and pot conditions (Patade et al, 2011). However, the responses for leaf area have varied among different genotypes and drought intensities (Endres et al, 2018). Drought tolerant research on cowpeas grown in a hydroponics system was reported by Ogbonnaya et al (2003), who found that drought-resistant varieties could better maintain leaf area than a susceptible variety.…”
Section: Above-ground Traitsmentioning
confidence: 99%
“…The sensitivity of sugarcane to this abiotic factor is determined by the genetic code. In the condition of introduced and natural water deficit, the varieties, RB72-454 and RB85-5536, produce less leaves than SP79-1011, RB86-7515, RB85-5113, and RB92-579, which present higher loads and provide more tillers per plant (Endres et al, 2018). Under water stress, B. subtilis and B. megaterium induce growth in sugarcane cultivation by stimulating the synthesis of acidic invertases, enzymes that hydrolyze sucrose, polysaccharide stored in photosynthetic tissues, and incomplete stem parenchyma.…”
Section: Development Of Sugarcane Plants Inoculated With B Aryabhattaimentioning
confidence: 99%
“…Although technically efficient, this propagation method is unlikely to be sensitive to water deficit; in planting, there will be intense dehydration of PSS, if the availability of water in the soil is not sufficient to the meet evapotranspiration demand of the crop. The main consequences are undoubtedly: generalized mortality, unsatisfactory productive yield of high-quality raw material, and inevitably unsustainable cost of production (Agroanalysis, 2017;Endres et al, 2018).…”
Section: Introductionmentioning
confidence: 99%